2020
DOI: 10.1001/jamanetworkopen.2020.0567
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Myopic Maculopathy Among Adults in a Russian Population

Abstract: IMPORTANCE Although myopic maculopathy has become a major cause of vision impairment worldwide, few data from Russia and Central Asia on the prevalence of myopic maculopathy have been available. OBJECTIVE To assess the prevalence of myopic maculopathy and its associations with ocular and systemic parameters in a population in Russia. DESIGN, SETTING, AND PARTICIPANTS The Ural Eye and Medical Study, a population-based casecontrol study, was conducted in rural and urban areas in Bashkortostan, Russia, from Octob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
80
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

5
4

Authors

Journals

citations
Cited by 66 publications
(91 citation statements)
references
References 26 publications
6
80
0
Order By: Relevance
“…3). For the latter analysis, we included only the moderately to highly myopic individuals (with a cut-off value of 25.5 mm), since the prevalence of myopic complications, mainly myopic maculopathy and myopia-associated optic neuropathy, markedly increases with longer axial length beyond an axial length of approximately 25.5 mm or 26 mm 18 . In the multivariable analysis, we dropped, due to collinearity the parameters of serum concentration of glucose (prevalence of diabetes), creatinine (chronic kidney disease) and hemoglobin (anemia), body weight (body mass index), and refractive error (axial length).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…3). For the latter analysis, we included only the moderately to highly myopic individuals (with a cut-off value of 25.5 mm), since the prevalence of myopic complications, mainly myopic maculopathy and myopia-associated optic neuropathy, markedly increases with longer axial length beyond an axial length of approximately 25.5 mm or 26 mm 18 . In the multivariable analysis, we dropped, due to collinearity the parameters of serum concentration of glucose (prevalence of diabetes), creatinine (chronic kidney disease) and hemoglobin (anemia), body weight (body mass index), and refractive error (axial length).…”
Section: Resultsmentioning
confidence: 99%
“…3 ). For the latter analysis, we included only the moderately to highly myopic individuals (with a cut-off value of 25.5 mm), since the prevalence of myopic complications, mainly myopic maculopathy and myopia-associated optic neuropathy, markedly increases with longer axial length beyond an axial length of approximately 25.5 mm or 26 mm 18 .
Figure 1 Graph showing the association between the prevalence of moderate to severe vision impairment (visual acuity < 6/18 but ≥ 3/60 in the better eye) in the Ural Eye and Medical Study, stratified by age and gender.
…”
Section: Resultsmentioning
confidence: 99%
“…The results of the present study may have clinical implications. Myopic maculopathy and optic nerve atrophy in association with high axial myopia have become some of the most common causes of irreversible vision impairment and blindness 48‐50 . The most important risk factor for the development and progression of myopic maculopathy and highly myopic optic nerve damage is a long axial length and further elongation 51‐53 .…”
Section: Discussionmentioning
confidence: 99%
“…R ecent population-based studies and their meta-analysis have revealed that pathologic myopia is one of the most common causes for irreversible blindness worldwide. [1][2][3] According to the META-analysis for Pathologic Myopia Study Group, the fundus changes in pathologic myopia can be differentiated into category 1, characterized by an increased fundus tessellation, category 2 showing a diffuse chorioretinal atrophy in the macular region, category 3 with patchy atrophies located in the extrafoveal region and representing the ophthalmoscopical equivalent of a smaller central region with a Bruch membrane (BM) defect and a larger defect in the retinal pigment epithelium (RPE) cell layer, and category 4 with patchy atrophy located in the fovea. 4 Plus lesions are lacquer cracks, choroidal neovascularization, and a macular scar (Fuch spot).…”
mentioning
confidence: 99%